Examining fifteen years of ethics research in the Journal of Accountancy: 2002 to 2016 - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2018)
In the past fifteen years, ethics has come under the spotlight in the accounting profession. In this study, I examine ethics research in accounting by looking at publications in the Journal of Accountancy, a leading professional journal in accounting, over the period from 2002 to 2016. I found that 32 out of 4,851 (0.66%) articles published in the journal were ethics-focused. Further, I observed spikes in the percentage of ethics-focused articles in the years 2003 and 2009/2010, following key events such as the passing of SOX and the global financial crisis. I also perform content analysis of the ethics-focused articles by categorizing them to one of four research areas: (1) code of conduct, (2) corporate culture, (3) ethical decision making, and (4) reputation management. Given that the majority of ethics-focused articles published relate to encouraging ethical behaviour among accounting professionals, my results suggest that such articles present a good source of information that accounting professionals can turn to when making decisions which have ethical implications. My study makes important contributions by providing insights into the overall proportion of ethics-focused articles that is published in the journal, and assesses the progress/evolution of ethics research over the time period. From a broader perspective, the findings in my study also add to the overall literature on business ethics by highlighting significant themes that accounting researchers have focused on. In addition, it provides insights into how ethics research has been incorporated into the area of accounting, particularly from a practice perspective. It also highlights four key areas of ethics research in accounting, and helps identify areas of future research.